Effects of single and multiple transplantations of human umbilical cord mesenchymal stem cells on the recovery of ovarian function in the treatment of premature ovarian failure in mice - Xiaodan Lv; Chunyi Guan; Ying Li; Xing Su; Lu Zhang; Xueqin Wang; Hong-Fei Xia; Xu Ma (BMC, 2021)
Abstract Background Currently, there is no effective treatment for premature ovarian failure (POF), and stem cell therapy is considered the most promising treatment. Human umbilical cord blood mesenchymal stem cells (hUC-MSCs) have shown good regenerative ability in various diseases, including POF; however, their underlying mechanism and dosage for POF treatment remain unclear. This study aimed to compare the effect of single and multiple injections of hUC-MSCs on ovarian function repair in chemotherapy-induced POF. Methods Female mice were intraperitoneally injected with 30 mg/kg busulfan and 120 mg/kg cyclophosphamide (CTX) to induce POF. In the single hUC-MSC injection group, hUC-MSCs were transplanted into mice D7 after CTX and busulfan administration, while in the multiple injection group, hUC-MSCs were transplanted on D7, D14, and D21 after CTX and busulfan administration. We evaluated the ovarian morphology, fertility, follicle-stimulating hormone and estradiol concentrations, follicle count, POF model, and cell transplantation results. In addition, real-time polymerase chain reaction, immunohistochemistry, and miRNA and mRNA chips were used to evaluate the effect of the cell therapy. Results Ovary size, number of follicle at all developmental stages, and fertility were significantly reduced in the POF group compared with the control. Under hUC-MSC treatment, the ovarian morphology and follicle count were significantly restored, and fertility was significantly increased. By comparing the single and multiple hUC-MSC injection groups, we found that the anti-Müllerian hormone and Ki-67 levels were significantly increased in the multiple hUC-MSC group on D60 after chemotherapy. The expression of stimulating hormone receptors, inhibin α, and inhibin β was significantly restored, and the therapeutic effect was superior to that of the single hUC-MSC injection group. Conclusion These results indicate that hUC-MSCs can restore the structure of injured ovarian tissue and its function in chemotherapy-induced POF mice and ameliorate fertility. Multiple hUC-MSC transplantations have a better effect on the recovery of ovarian function than single hUC-MSC transplantation in POF.